HUBUNGAN KADAR INTERLEUKIN 6 DENGAN KADAR BESI SERUM PENDERITA ANEMIA PADA PENYAKIT KRONIK - Wibawa, I Putu Budi; Bakta, I Made (journal of internal medicine, 2008)
Anaemia of chronic disease is the second most prevalence after iron deficiency anaemia. It is a commonproblem faced because it decreasing the life quality. The pathofisiology of anaemia of chronic disease is same inmalignancy, chronic infection and chronic inflammation. There is immune driven pathway. Releasedproinflammation cytokine cause hypoferemia and hyperferitinaemia which the result is anaemia. The Objectiveis to determine the correlation of IL-6 with serum iron and haemoglobin in anaemia of chronic disease patien atSanglah General Hospital, Denpasar – Bali. The Cross sectional analytic study performed to search thecorrelation of IL-6 with serum iron and haemoglobin. Descriptive statistical test performed to descript thesample characteristic and the distribution frequency of many variable. Spearman correlation used with p < 0.05is significant. From 25 samples, there are 12 man (48%) and 13 woman (52%). The mean of samples age is49.20 ± 17.95 years old. The most prevalence diagnosis is lung TB, 8 samples (32%). The mean of IL-6 is 39.32± 48.66 pg/mL. The mean of serum iron is 42.48 ± 22.09 ug/mL. The mean of hemoglobin is 10.49 ± 1.47 g/dL.The mean of feritin is 607.62 ± 841,01 ng/mL. The mean of monocyte count is 0,91 ± 0,95 cell/mm3. Thecorrelation of IL-6 with serum iron is not significant (r -0.05, p 0325). The correlation of IL-6 withhaemoglobin is not significant too (r -0.027, p=0.898). There are possibility cause, first, the gradation ofmalignancy, chronic infection, chronic inflammation is not performed. Second, other inflammation cytokine isnot checked. Comorbid disease also may take a place. We conclude the correlation of IL-6 with serum iron andhaemoglobin is not significant.